Hydrodynamic Response Assessment of Floating Photovoltaic System Subjected to Environmental Loadings - Ghonim, Ossama Yehia Gouda Ahmed; Al-Yacouby, Ahmad Mahamad (Journal of Advanced Research Design, 2025)
Floating Photovoltaic systems (FPVs) represent a novel integration of solar energy technology with aquatic environments, marking a pivotal advancement in renewable energy applications. This paper introduces a new design for the floating system, specifically engineered to optimize performance under hydrodynamic conditions. Despite the significant focus on the field, the complex hydrodynamics of FPVs, particularly their resilience against varying offshore conditions, remain inadequately explored. This study seeks to bridge this knowledge gap by using an Excel-based analytical model to investigate how changes in design parameters, such as water depth and wave height, affect the surge, heave and pitch responses of the proposed design. Our findings indicate that water depth variations predominantly affect surge movement, while wave height significantly influences all hydrodynamic responses of the floater.